Determinants of Financial Performance: The Moderating Role of Institutional Ownership in Construction Firms Listed on the Indonesia Stock Exchange - Zikra, Nabilah Ridhanti; Kurniasih, Augustina (International Journal of Social and Management Studies, 2025)
This study examines the influence of Environmental, Social, and Governance (ESG) factors, leverage (DER), Enterprise Risk Management (ERM), and firm size on financial performance (ROA) among construction companies listed on the Indonesia Stock Exchange (BEI) from 2021 to 2024, with institutional ownership as the moderating variable. The research population comprised 29 BEI-listed construction firms in 2024, from which 10 companies were selected as samples via purposive sampling, yielding 40 observations (panel data for 2021–2024). A quantitative approach was employed using panel data regression and moderated regression analysis (MRA). The results indicate that DER exerts a negative and significant effect on ROA, whereas ESG, ERM, and firm size show no significant influence on ROA. Institutional ownership moderates the effects of ERM and firm size on ROA but does not moderate the relationships between ESG or DER and ROA. These findings underscore the importance of effective capital structure management, alongside the implementation of risk management practices and business scale enhancement under institutional investor oversight, to foster sustainable financial performance in the construction sector.